2014
DOI: 10.1523/jneurosci.0953-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Deep Cerebellar Stimulation Promotes Long-Term Potentiation, Microstructural Plasticity, and Reorganization of Perilesional Cortical Representation in a Rodent Model

Abstract: Control over postinjury CNS plasticity is a major frontier of science that, if conquered, would open new avenues for treatment of neurological disorders. Here we investigate the functional, physiological, and structural changes in the cerebral cortex associated with chronic deep brain stimulation of the cerebellar output, a treatment approach that has been shown to improve postischemia motor recovery in a rodent model of cortical infarcts. Long-Evans rats were pretrained on the pasta-matrix retrieval task, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 49 publications
11
78
1
Order By: Relevance
“…entorhinal cortex (EC) or anterior nucleus of the thalamus (ANT), modulate hippocampus-dependent memory and neurogenesis [8,9,23,24]. Recent work has also demonstrated that DBS at other targets, including the subthalamic nucleus (STN), the ventromedial prefrontal cortex (vmPFC) and the cerebellum, modulates gene and protein expression [25][26][27][28]. However, the mechanisms of action of DBS in general and for forniceal stimulation in particular remain unknown.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…entorhinal cortex (EC) or anterior nucleus of the thalamus (ANT), modulate hippocampus-dependent memory and neurogenesis [8,9,23,24]. Recent work has also demonstrated that DBS at other targets, including the subthalamic nucleus (STN), the ventromedial prefrontal cortex (vmPFC) and the cerebellum, modulates gene and protein expression [25][26][27][28]. However, the mechanisms of action of DBS in general and for forniceal stimulation in particular remain unknown.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Deep brain stimulations targeting the thalamus (Th) and periaqueductal gray matter for post-stroke movements and neuropathic pain have demonstrated efficacy in human studies [59][60][61]. Deep brain stimulations in the cerebellar dentate nucleus in rats have also been shown to promote post-stroke recovery and enhance synaptic plasticity and reorganization in the perilesional cortex [62][63][64][65].…”
Section: Current Brain Stimulation Techniques Used To Study Stroke Rementioning
confidence: 99%
“…2). Electrical stimulation of the dentate nucleus in rats has been shown to promote recovery and enhance plasticity [62][63][64][65]. Tracing studies using the rabies virus have indicated that different divisions of the dentate nucleus mediate different functions.…”
Section: Benefits Of Optogeneticsmentioning
confidence: 99%
“…Such findings have important physiological implications, as LCN LFPs during reaching and grasp have not been studied to date. Furthermore, these findings represent an important technical milestone by advancing ongoing translational work in chronic stimulation of the LCN as a treatment for post-injury motor rehabilitation (Cooperrider et al, 2014; Machado et al, 2013) towards a closed-loop stimulation therapy, wherein stimulation is triggered by a neural signal.…”
Section: Introductionmentioning
confidence: 96%